SARS-CoV-2 Infected Cases with Untraceable Epidemic Origin: Its Values, Identification and TCM Treatment in Preventing Recurrence - Li Kai; Pierre Sirois; Dai Ai-Guo; Liao Duan-Fang (KeAi Communications Co., Ltd., 2020)
During the outbreak of coronavirus disease 2019 (COVID-19), the identification of a SARS-CoV-2 infected case with untraceable epidemic origin has three values: (1) the region has community transmission of the virus; (2) a certain portion of population in the community is getting immunized and more individuals have already been immunized; (3) an unpredictable future risk exists for regions where there are no infected cases with untraceable epidemic origin. Minimizing or avoiding the aggregation infection through individuals with no clinical symptoms is crucial and possible as its occurrence is mainly attributed to the local environment as opposed to the super spreader with or without clinical symptoms. As infected cases are not necessarily positive with gene test by definition, proper application of gene test is crucial in the identification of asymptomatic cases. In the early stage of an outbreak of infectious disease, gene test can be used to identify asymptomatic cases but it should not be used to exclude cases with typical clinical symptoms and signs. In the middle or late stages of an outbreak gene test should be applied in evaluation of infection rate of the population of a region, in addition to be used in spreader identification and isolation. Although asymptomatic cases are attributed to the overwhelming effect of personalized defense against pathogens, they are still a source of infection. Asymptomatic cases are considered to be Qi deficiency and with lingering toxicity in traditional Chinese medicine (TCM). Treatment in such cases, typically, involves therapy focused on replenishing the Qi, tonifying the lung, clearing the fever, and detoxification in order to return to a normal health condition. The recommended Chinese medicines include Qing Fei Pai Du Decoction, Yi Qi Qu Du Decoction, Xuan Fei Bai Du Granule, Lian Hua Qing Wen Capsule (Granule), and Jin Hua Qing Gan Granule, etc.